The Implementation of e-Feedback in Improving Students’ Writing Quality: the Importance and Perspective - Elhawwa, Tazkiyatunnafs; Sabarun, Sabarun; Pionera, Mutiarani; Khunaifi, A’am Rifaldi (English Language in Focus (ELIF), 2024)
In the digital age, where conventional methods of feedback may no longer be sufficient, e-feedback presents a modern approach that aims to provide clarity and efficiency. This study investigates the effectiveness of electronic feedback, or e-feedback, in enhancing students' writing skills. This descriptive qualitative study involved 25 students from a university in Central Kalimantan and used a diverse range of data collection methods, including open-ended and closed-ended questionnaires, observations, interviews, and analysis of student papers. Throughout ten instructional meetings, participants expressed positive feedback regarding the e-feedback method, highlighting its time-saving nature, clarity, and user-friendliness. They particularly valued the opportunity to correct their mistakes, with the use of color-coded highlights to understand different types of errors adding an engaging element to the feedback process. While the advantages of e-feedback were widely recognized, some participants noted a desire for more verbal explanations to accompany their written feedback. Overall, the findings indicate that e-feedback not only boosts students' enthusiasm and participation in writing classes but also significantly improves their writing skills.